Key factors leading to reduced recruitment and retention of health professionals in remote areas of Ghana: a qualitative study and proposed policy solutions - Dzodzomenyo Mawuli; Gyan Kofi; Koomson Elizabeth; Mutumba Massy; Asabir Kwesi; Snow Rachel C; Kruk Margaret; Kwansah Janet (BMC, 2011)
Abstract Background The ability of many countries to achieve national health goals such as the Millennium Development Goals remains hindered by inadequate and poorly distributed health personnel, including doctors. The distribution of doctors in Ghana is highly skewed, with a majority serving in two major metropolitan areas (Accra and Kumasi), and inadequate numbers in remote and rural districts. Recent policies increasing health worker salaries have reduced migration of doctors out of Ghana, but made little difference to distribution within the country. This qualitative study was undertaken to understand how practicing doctors and medical leaders in Ghana describe the key factors reducing recruitment and retention of health professionals into remote areas, and to document their proposed policy solutions. Methods In-depth interviews were carried out with 84 doctors and medical leaders, including 17 regional medical directors and deputy directors from across Ghana, and 67 doctors currently practicing in 3 regions (Greater Accra, Brong Ahafo, and Upper West); these 3 regions were chosen to represent progressively more remote distances from the capital of Accra. Results and discussion All participants felt that rural postings must have special career or monetary incentives given the loss of locum (i.e. moonlighting income), the higher workload, and professional isolation of remote assignments. Career 'death' and prolonged rural appointments were a common fear, and proposed policy solutions focused considerably on career incentives, such as guaranteed promotion or a study opportunity after some fixed term of service in a remote or hardship area. There was considerable stress placed on the need for rural doctors to have periodic contact with mentors through rural rotation of specialists, or remote learning centers, and reliable terms of appointment with fixed end-points. Also raised, but given less emphasis, were concerns about the adequacy of clinical equipment in remote facilities, and remote accommodations. Conclusions In-depth discussions with doctors suggest that while salary is important, it is career development priorities that are keeping doctors in urban centers. Short-term service in rural areas would be more appealing if it were linked to special mentoring and/or training, and led to career advancement.